2008
DOI: 10.1111/j.1939-1676.2008.0146.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Norepinephrine and Combined Norepinephrine and Fenoldopam Infusion on Systemic Hemodynamics and Indices of Renal Function in Normotensive Neonatal Foals

Abstract: Background: Norepinephrine increases arterial blood pressure but may have adverse effects on renal blood flow. Fenoldopam, a dopamine-1 receptor agonist, increases urine output in normotensive foals. The combination of norepinephrine and fenoldopam may lead to improved renal perfusion compared with an infusion of norepinephrine alone. The combined effects of these drugs have not been reported in the horse.Hypothesis: Norepinephrine will alter the hemodynamic profile of foals without affecting renal function. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…Other significant changes included modest decreases in heart and respiratory rates at variable times. These changes were not perceived as clinically important and were likely related to the CRI of detomidine, which is known to cause cardiovascular and respiratory depression . In addition, transient arrhythmias were noted during RRT.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other significant changes included modest decreases in heart and respiratory rates at variable times. These changes were not perceived as clinically important and were likely related to the CRI of detomidine, which is known to cause cardiovascular and respiratory depression . In addition, transient arrhythmias were noted during RRT.…”
Section: Discussionmentioning
confidence: 94%
“…Creatinine clearance based on body weight (CrCl; mL/kg/min) of the effluent fluid: CrCl=(Ultrafiltrate [Cr]Plasma [Cr]×Dialysate output [mL]Time [minute]Body weight (kg)) …”
Section: Methodsmentioning
confidence: 99%
“…Still other studies demonstrated a NE-induced reduction in HR in healthy humans (30)(31)(32), normal and hypertensive subjects (33), and in several animal studies (14,(34)(35)(36). The HR reduction in all these studies was attributed to a baroreceptor-mediated central sympathetic withdrawal triggered by the NE-induced increased blood pressure (34,36). However, such baroreceptor-induced change in HR is accompanied by vasodilation of veins and arterioles (37).…”
Section: Co Decrease By Nementioning
confidence: 94%
“…Noradrenaline and adrenaline are known to affect cardiovascular function in fetal and newborn foals (Hollis et al . 2006; O'Connor et al .…”
Section: Sympatho‐adrenal Medullary Axismentioning
confidence: 99%
“…They raise blood pressure by increasing both systemic vascular resistance and heart rate at all ages studied from mid gestation to 14 days after birth, although they are more effective pressor agents after than before birth (O'Connor et al . 2005, 2006; Hollis et al . 2006).…”
Section: Sympatho‐adrenal Medullary Axismentioning
confidence: 99%